New Surface-Plasmon-Polariton-Like Acoustic Surface Waves at the Interface Between Two Semi-Infinite Media - KIEŁCZYŃSKI, Piotr (Archives of Acoustics, 2022)
This paper presents theory of new shear horizontal (SH) acoustic surface waves that propagate along the interface of two semi-infinite elastic half-spaces, one of which is a conventional elastic medium and a second one an elastic metamaterial with a negative and frequency dependent shear elastic compliance. This new surface waves have only one transverse component of mechanical displacement, which has a maximum at the interface and decays exponentially with distance from the interface. Similar features are also shown by the acoustic shear horizontal Maerfeld-Tournois surface waves propagating at the interface of two semi-infinite elastic media due to the piezoelectric effect that should occur in at least one semi-space. The proposed new shear horizontal acoustic surface waves exhibit also strong formal similarities with the electromagnetic surface waves of the surface plasmon polariton (SPP) type, propagating along a metal-dielectric planar interface. In fact, the new shear horizontal elastic surface waves possess a large number of properties that are inherent for the SPP electromagnetic surface waves, such as strong subwavelength concentration of the wave field in the proximity of the guiding interface, low phase and group velocity etc. As a result, the new shear horizontal acoustic surface waves can find applications in sensors with extremely high sensitivity, employed in measurements of various physical parameters, such as viscosity of liquids, as well as in biosensors, chemosensors, or a near field acoustic microscopy (subwavelength imaging) and miniaturized devices of microwave acoustics.